Manajemen Kelas MIN 1 Palangka Raya - Muhammad Tri Ramdhani; Widya Widya (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Classroom management is a conscious effort to plan, organize, actualize, and implement supervision or supervision of programs and activities in the classroom so that the learning process can take place systematically, effectively, and efficiently, so that all potential learners can be optimized. Classroom management activities include two activities that outline consists of First learner settings, Both facility settings. Results from the observation of students in MIN 1 Palangkaraya students in class III amounted to 30-39 students so that class management is less effective, and students in the class are doing activities that interfere like chatting with friends so that in the learning process difficult to understand. And also the results of observation of facilities and infrastructure in MIN 1 Palangkaraya, for the facilities are still sufficient such as adequate building for learning process activities, then the absence of LCD facilities in the class tesebut. So less supportive in teaching and learning process. While the infrastructure in MIN 1 Palangkaraya such as yard, school park, the road to school is adequate. In addition, the techniques used in data collection are interviews, observation techniques, note notes, and documentation.